2017
DOI: 10.1007/s00128-017-2219-y
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Concentrations in Tree Leaves and Lichen Collected Along a Metal Pollution Gradient Near Olkusz (Southern Poland)

Abstract: The aim of the study was to assess the metal pollution in the vicinity of the Bukowno smelter near Olkusz in southern Poland. Birch and oak leaves, pine needles and a lichen Hypogymnia physodes, overgrowing pine bark were collected at stands at different distances from the smelter and analysed for cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn) content. Concentrations of metals in the lichen were usually higher than in the tree leaves/needles and decreased with distance from the smelter, apart from the Cu c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Rafati et al [33] reported that the accumulation of Cd and Cr was relatively higher in defoliated leaves than in the green leaves of Populus alba. High concentration of Cu has also been reported in leaves of an oak species growing at a contaminated site [34]. In the present study, the Cu concentration in the wood rings 1 and 2 varied from 38 to 41% (Fig.…”
Section: Plant Tissuessupporting
confidence: 75%
“…Rafati et al [33] reported that the accumulation of Cd and Cr was relatively higher in defoliated leaves than in the green leaves of Populus alba. High concentration of Cu has also been reported in leaves of an oak species growing at a contaminated site [34]. In the present study, the Cu concentration in the wood rings 1 and 2 varied from 38 to 41% (Fig.…”
Section: Plant Tissuessupporting
confidence: 75%
“…Study sites are polluted with several metals, mainly Cd, Zn, and Pb (Grześ 2009 ; Zakrzewska and Klimek 2018 ); each one is characterized with a different toxicity to living organisms. In order to easy compare metal pollution and toxicity between stands, the soil metal contents on each plot was integrated and expressed by a toxicity index (TI) as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Although several authors studied the atmospheric deposition regarding both the quantities and elemental composition of dust [ 21 , 22 , 23 , 24 , 25 ], the comparisons among cities are not widespread, and finding the differences in a multivariate approach is rare. It is vital to reveal how the geochemical background, the source of pollution, and the investigated plant species can influence the distribution and cross-connections of heavy metals in different environments.…”
Section: Introductionmentioning
confidence: 99%